The Urgency of Legal Certainty for Traditional Healthcare Who Do Not Have a Practice License - Donald Willem Srianto Aronggear; Abdullah Sulaiman (CV. Media Digital Publikasi Indonesia, 2025)
This study analyzes the importance of updating and strengthening regulations related to traditional healer practice permits in Indonesia to ensure the quality and safety of conventional health services. Normative research methods and a statute approach in this study examine existing regulations, challenges in their implementation, and the need for strict sanctions for violators of permits to protect the public from unauthorized and dangerous health practices. It highlights the importance of supervision by the Health Office and socialization to traditional healers and the public regarding licensing obligations and safety standards.